Answer:
m= 1/10
Step-by-step explanation:
1. Move the terms so that will be 3m - 2m=-1/2 + 3/5
2. Subtract the m values so that will be 3m - 2m= 1 or m
3. Calculate the sum.
4. So the answer will be m= 1/10. M because we subtracted 2 from 3 which make us 1 so we say it m and 1/10 by doing 1/2 + 3/5.
Answer:
30 because 3 x 5=15 then x2 it's 30
Answer:
A. (f-g)(x) = -7x -3
Step-by-step explanation:
(f -g)(x) = f(x) -g(x) = (-3x -5) -(4x -2)
= -3x -5 -4x +2
= -3x -4x -5 +2
(f -g)(x) = -7x -3
<h3>Answer:</h3>
D
<h3>Explanation:</h3>
The graph of |x| opens upward. Your graph is vertically stretched by a factor of 3 and translated downward 1 unit.
Graphs B and D open upward, but only graph D is translated downward (not upward, as in B).
Answer:
6
Step-by-step explanations:
The remainder is what is left over after dividing whatever from d. So if you add one to d, then the remainder would increase from 5 to 6.
Hope this helps.